2024
DOI: 10.1021/acssuschemeng.3c07446
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Based Chrome-Free Tanning Agent Results in the Sustainable and Cleaner Production of Eco-Leather

Xugang Dang,
Heng Qiu,
Shuguang Qu
et al.

Abstract: This study aimed to pioneer the development of an innovative, ecofriendly, and chrome-free tanning agent, with a focus on promoting sustainable practices in ecological leather production. Two novel biomass-derived tanning agents, namely, β-TCD and β-GCD, were synthesized through a one-pot grafting process involving environmentally friendly epoxy monomers: triglycidyl isocyanurate (TGIC) and glycerol triglycidyl ether (GTE). Characterization through various analytical methods, including FTIR, 1 H NMR, XPS, GPC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similarly, Ding et al reported on the utilization of a biomass-derived aldehyde tanning agent (BAT-iDP) in leather processing, , leading to in situ dyeing properties. A β-cyclodextrin-based tanning agent was also identified as a potent and environmentally friendly alternative to chromium-based tanning agents . Several chrome-free tanning agents, such as wrench-like epoxy-terminated organic chrome-free tanning agent (HHTT-EGDE-CP), starch-based chrome-free tanning agent, chitosan, and glycerol triglycidyl ether-based tanning agent, have been reported for a cleaner tanning process. However, all of these reported systems were developed for chrome-free tanning processes, highlighting the existing gap in sustainable dyeing solutions applicable to a wide range of substrates, including chrome-tanned, vegetable-tanned, and chrome-free systems.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ding et al reported on the utilization of a biomass-derived aldehyde tanning agent (BAT-iDP) in leather processing, , leading to in situ dyeing properties. A β-cyclodextrin-based tanning agent was also identified as a potent and environmentally friendly alternative to chromium-based tanning agents . Several chrome-free tanning agents, such as wrench-like epoxy-terminated organic chrome-free tanning agent (HHTT-EGDE-CP), starch-based chrome-free tanning agent, chitosan, and glycerol triglycidyl ether-based tanning agent, have been reported for a cleaner tanning process. However, all of these reported systems were developed for chrome-free tanning processes, highlighting the existing gap in sustainable dyeing solutions applicable to a wide range of substrates, including chrome-tanned, vegetable-tanned, and chrome-free systems.…”
Section: Introductionmentioning
confidence: 99%